Impact of Intestinal Bacteria on Levodopa Pharmacokinetics in LCIG Therapy. Issue 3 (20th February 2022) - Yamanishi, Yuki; Choudhury, Mohammed Emamussalehin; Yoshida, Akira; Hosokawa, Yuko; Miyaue, Noriyuki; Tada, Satoshi; Ando, Rina; Murakami, Shinobu; Miyamoto, Hitoshi; Nagai, Masahiro
ABSTRACT: Background: Levodopa‐carbidopa intestinal gel (LCIG) therapy is used in advanced Parkinson's disease (PD) and consists of continuous administration of levodopa directly into the jejunum through a percutaneous endoscopic gastro‐jejunal (PEG‐J) tube. Recently, the metabolism of levodopa by Enterococcus faecalis ( E. faecalis ) has been reported. Intestinal bacteria can also affect this therapy. Objectives: To investigate intestinal bacteria and examine its impact on levodopa blood concentration in patients with PD receiving LCIG therapy. Methods: We enrolled 6 patients receiving LCIG therapy in our department. After PEG‐J tube replacement, intestinal bacteria were collected from the tip of the tube and were identified using culture and polymerase chain reaction (PCR) tests. Moreover, the presence of tyrosine decarboxylase, which metabolizes levodopa, was also confirmed by PCR test. The ability of these bacteria to metabolize levodopa was confirmed in vitro. Levodopa blood concentrations were also examined before PEG‐J tube replacement. Results: Bacteria were detected in all 6 patients. E. faecalis was present in 4 patients. Moreover, tyrosine decarboxylase was detected in 2 patients. The identified bacteria displayed in vitro metabolization to dopamine in the 4 E. faecalis positive samples. The addition of carbidopa did not inhibit the metabolism of levodopa. However, there was no difference in the mean blood concentration of levodopa, regardless of the presence of E. faecalis . Conclusions: We found bacteria, including E. faecalis in the PEG‐J tube. We observed levodopa metabolism in vitro, but there was no association with levodopa blood concentration. The effect of intestinal bacteria may be limited in patients receiving LCIG therapy.